Ascorbic acid is associated with favourable hormonal profiles among infertile males - Rastegar Panah, Matineh; Tahir, Irtaza; Garcia-Bailo, Bibiana; Lo, Kirk; Jarvi, Keith; El-Sohemy, Ahmed (Frontiers in Reproductive Health, 2023)
Introduction Infertility affects about 16% of North American couples, with the male factor contributing to ∼30% of cases. Reproductive hormones play an integral role in regulating the reproductive system and consequently, fertility. Oxidative stress reduces testosterone synthesis, and reduction in oxidative stress can improve hormone profiles. Ascorbic acid is a potent antioxidant that accounts for up to 65% of seminal antioxidant activity; however, its effects on reproductive hormones in humans are unknown. Methods The objective was to determine the association between serum ascorbic acid concentrations and male reproductive hormones. We conducted a cross-sectional study involving infertile males (n = 302) recruited from Mount Sinai Hospital, Toronto. Serum was analyzed for ascorbic acid, luteinizing hormone (LH), follicular stimulating hormone (FSH), total testosterone (TT), prolactin and estradiol. Statistical analyses included Spearman's rank correlations, linear regressions, logistic regressions, simple slope and Johnson-Neyman procedures. Results After adjusting for covariates, ascorbic acid was inversely associated with LH (P = 0.01). Ascorbic acid was positively associated with TT only among males over the age of 41.6 years (P = 0.01). Discussion Our findings show that ascorbic acid is associated with higher testosterone levels and improved androgenic status in infertile males, and some of the effects appear to be age dependent.